STRUCTURAL FAMILY THERAPY AS MEDIATION PROCESS FOR MARITAL CONFLICT (CASE STUDY) - Zuhrotun Ulya (Journal of Psychiatry Psychology and Behavioral Research, 2020)
Divorce cases were dominated by marital conflict by partner disputes, miscommunication, economic problems, etc. The mediation process as one of the stages of the divorce process allows couples to discuss about their decisions. This will be followed by one of the couples come looking for help due to their psychological problems to psychiatrist or psychologist. Tracing the problem lies in the pattern of relationship structure and family intimacy that triggers marital conflict. Structural Family Therapy (SFT) is a psychotherapy modality that is expected to improve the structure of sub-system relations so that it appears as an effort to mediate marital conflict. This research will try to find out the results of Structural Family Therapy as an effort to mediate marital conflict through evaluation of the structure relationship and family intimacy.Â  This research was qualitative (case study) which conduct to 3 married couples, registered as patient at Psychiatry Clinic Universitas Brawijaya Hospital, research held for 20 weeks (December 2018 - April 2019). Evaluation from structure of the family area (family structure, system flexibility, resonance, life context, level of development and transaction patterns) and family intimacy. Post SFT evaluation, there was not only increasing of structure area and family intimacy in all cases but also slightly resolve of marital conflicts. This case study need to follow up in long term evaluation after SFT.Keywords:Â  structural family therapy, marital conflict, mediation.